Russian and Tajic word formation in linguistic research works - K E Ismailova (Polylinguality and Transcultural Practices, 2015)
This article discusses the history of the study of word formation in Russian and Tajik languages. Peculiarities of word formation of two languages with the aim of typological studies of different languages is presented.